2000
DOI: 10.1159/000029913
|View full text |Cite
|
Sign up to set email alerts
|

Cutaneous Inflammation and Proliferation in vitro: Differential Effects and Mode of Action of Topical Glucocorticoids

Abstract: The nonhalogenated double ester of prednisolone, prednicarbate (PC), is the first topical glucocorticoid with an improved benefit/risk ratio verified clinically and in vitro. To evaluate if this is due to unique characteristics of this steroid, a new compound created according to an identical concept, prednisolone 17-ethylcarbonate, 21-phenylacetate (PEP), and the new halogenated monoester desoximetasone 21-cinnamate (DCE) were tested and compared to PC, desoximetasone (DM) and betamethasone 17-valerate (BMV).… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0
3

Year Published

2002
2002
2017
2017

Publication Types

Select...
10

Relationship

1
9

Authors

Journals

citations
Cited by 42 publications
(41 citation statements)
references
References 27 publications
0
38
0
3
Order By: Relevance
“…Prednicarbate and prednisolone 17-ethylcarbonate primarily exert their anti-inflammatory activity by inhibiting the synthesis of IL-1· and IL-6 in keratinocytes [3,7,28]. Due to its high activity, native prednicarbate cannot be regarded as a prodrug anymore [28].…”
Section: Discussionmentioning
confidence: 99%
“…Prednicarbate and prednisolone 17-ethylcarbonate primarily exert their anti-inflammatory activity by inhibiting the synthesis of IL-1· and IL-6 in keratinocytes [3,7,28]. Due to its high activity, native prednicarbate cannot be regarded as a prodrug anymore [28].…”
Section: Discussionmentioning
confidence: 99%
“…Studies describing the effects of long-term use of glucocorticoids in HSEs, which were found to be as suitable models, have been described (Gysler et al, 1999;Lange et al, 2000;Lombardi Borgia et al, 2008). As another example, specific HSEs have been developed to simulate the disease conditions of psoriasis and skin cancer (Tab.…”
Section: Chip Technologymentioning
confidence: 99%
“…Discrepancies observed between in vitro experiments might be due to indirect effects of GCs on fibroblasts by affecting the synthesis or actions of various factors produced by other cell types. Yet, more recent studies show anti-proliferative effects of GCs on primary human fibroblasts 20,26 and HaCaT cells, a human keratinocyte cell line, 20 only. Beside their anti-proliferative effects in cutaneous cells, GCs also affect collagen metabolism.…”
Section: Determining the Atrophogenic Potential In Pre-clinical In VImentioning
confidence: 99%